EFFECT OF TURMERIC AND DRAGON FRUIT SKIN EXTRACTS IN DRINKING WATER ON BROILER BLOOD LIPID PROFILE - T., Hidayat,; Siti, N.W.; Suasta, I M. (Jurnal Peternakan Tropika; Vol 12 No 5 (2024): Vol. 12 No. 5 Tahun 2024; September - October, 2024)
The purpose of this study is to ascertain how broiler blood lipid profiles are affected when extracts from the peels of dragon fruit and turmeric are added to their water. Over the course of 28 days, the research was carried out in Gulingan Village, Mengwi District, Badung Regency. Four treatments and four replicates made up the completely randomized design (CRD) that was employed. This resulted in sixteen experimental units, each of which had four broilers. P0: Broilers without extract from the peel of dragon fruit and turmeric; P1: Broilers given 4% extract from the peel of turmeric in 1 liter of drinking water; P2: Broilers given 4% extract from the peel of dragon fruit in 1 liter of drinking water; P3: Broilers given 4% (2% extract from the peel of dragon fruit and 2% extract from turmeric) in 1 liter of drinking water. Blood triglyceride, HDL, LDL, and cholesterol levels were the variables that were observed. According to the study's findings, broiler blood cholesterol, LDL, HDL, and triglyceride levels were not significantly affected (P >0.05) by the addition of turmeric extract and dragon fruit peel to drinking water. The study's findings support the notion that giving broilers drinking water containing extracts from fruit peels and turmeric does not result in a change in their blood lipid profile.